Exploring depression literacy among Malaysian secondary school adolescents using a vignette‑based questionnaire - Zakaria, Rozanizam; Ubaidah, Aishah Nazurah; Abdul Rasyid, Khadijah; Ramli, Rawahah Husna (Malaysian Psychiatric Association, 2022)
Introduction: Mental health literacy is an important element for better recognition of illness and early intervention. This study is aimed at exploring the level of literacy on depression among a sample of secondary school adolescents in Malaysia and the factors that determine their level of literacy regarding depression.